(untitled) (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: Dental caries stand a persistent issue in clinical practice. It has been observed that dental caries is the primary reason for the failure of fixed dental prosthesis. Poor marginal fit and under steady materials increases the chances of repetitive caries around long-lasting temporary restorations. With the aim to preserve teeth from bacteria, researches have suggested to incorporate antibacterial and anticariogenic properties to dental materials. The motive of this research is to analyze the outcome of incorporation of Hexidine mouthwash, Profluorid varnish and Listerine mouthwash, individually to a non-eugenol based provisional cement, on the microleakage of temporary acrylic crowns. MATERIALS AND METHOD: Ten extracted with proper anatomic maxillary first premolar teeth were selected. Tooth preparation was done using standardization. Tooth colored auto-polymerising acrylic resin were used to create 40 temporary crowns. The prepared provisional crowns were splitted up into 4 categories of 10 crowns. Crowns were cemented on the prepared teeth after enriching with the three solutions individually. All samples were stored in proper100% humidity with the temperature of 37°C for at least 1 hour, then thermocycled 100 times with the temperature between 5°C and 55°C for 10 seconds time, and then after kept in 100% humidity at temperature of 37°C. Samples were placed in a container of 0.5% basic fuchsin, after that placed in an incubator with the temperature 37°C for minimum 6 hours. Cemented crowns were undergone for tensile dislodgment force with crosshead speed of 5mm/min by operating universal testing machine. After crown detachment, microleakage was checked. Dye penetration with maximum depth through the margins of teeth and the axial walls of was examined using standardized examination system. RESULT: Temporary cement enriched with PROFLUORID VARNISH has shown least degree of dye penetration, and control group without additives was having the highest mean degree of dye penetration. CONCLUSION: The present study concluded that profluoride varnish as an additive in provisional cements is the most effective in decreasing microleakage when temporary crowns are luted with non-eugenol temporary cement (provicol).